Squamanita umbonata (Fungi, Agaricales, Tricholomataceae), first record of Mexico - Cortés Pérez, Alonso; Guzmán, Gastón; Ramírez Guillén, Florencia (Instituto de Ecología, A.C., 2014)
The genus Squamanita is reported for the first time in Mexico, with S. umbonata from a pine-oak forest in the state of Veracruz. This mushroom has been cited from the United States  of America (Pennsylvania, Massachusetts), China and Japan. The Mexican specimen agrees well with the holotype of S.  umbonata, and with a specimen from the United States of America deposited in the herbarium NY studied by Bas.